(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article is devoted to the structural-morphological and syntactic features of embroidery terms. He analyzed embroidery terms lexically-morphologically into noun terms, adjective terms, and verb (name of action) terms. Instead, the meeting of these terms in folklore and artistic works was discussed.